“Effect of Virtual Reality Therapy as a therapeutic adjunct in rehabilitation program among traumatic lower-limb amputees”: A Parallel Open-label RCT - M Kalaivani, Avinash Dhargave, Saravana Moorthy*, Sushma Sagar, Subodh Kumar, Vivek Trikha, Rajesh Sagar, Chhavvi Sawhne (Innovative Journal of Medical and Health Sciences, 2020)
Amputation of the lower limb is a surgical procedure that is permanent and can be due to trauma or dysvascular causes. Loss of balance, reduced quality of life and phantom limb pain are the fundamental problems that an amputee of lower limb extremity deals with. (1) From 2007-2013, there were 310 lower limb amputation in JPN Apex Trauma Centre. Surprisingly, the numbers rose to 92 in 2017. In the year 2017&2018, the total no. of amputation cases increased to 412. Among them, there were 272 cases of lower limb amputations. (2) Loss of balance is due to the altered centre of gravity upon loss of a limb. (3) Limitations posed by body function and structure, thereby hindering participation in daily work activities affect the quality of life. Environmental and personal factors further influence these factors. (4) The standard rehabilitation is training through conventional exercises, which include weight-shifting exercises, dynamic balance exercises, stool stepping, braiding and gait exercises (5). These exercise programs are used to prevent vascular disease in people with amputation and their adaptation to amputation. Whatever the time of initiation of exercise is, it contributes to the physical as well as psychosocial wellbeing in general. It improves walking balance, circulation problems, control of prosthesis and energy consumption. (6)